84.2k views
3 votes
Help needed asap graph posted below

The graph of the function f(x) = x3 – 7x – 6 intersects the x-axis at the points (–2, 0), (–1, 0), and (3, 0) as shown.

Which expression is equivalent to x3 – 7x – 6?
A) (x – 1)(x – 2)(x – 3)
B) (x – 1)(x + 2)(x – 3)
C) (x + 1)(x – 2)(x – 3)
D) (x + 1)(x + 2)(x – 3)

Help needed asap graph posted below The graph of the function f(x) = x3 – 7x – 6 intersects-example-1

1 Answer

2 votes
Answer: D) (x+1)(x + 2)(x-3)

This is because the roots are x = -1, x = -2 and x = 3
Simply get all the numbers to each side to have 0 on the right side

x = -1 turns into x+1 = 0
x = -2 turns into x+2 = 0
x = 3 turns into x-3 = 0

The three factors are (x+1), (x+2) and (x-3)
Which leads to (x+1)(x+2)(x-3)

User LorTush
by
5.6k points